Indices of Industrial Output in Communist China - Chao, Kang (The Review of Economics and Statistics, 1963)
IT is a well-known fact that a high priority has been placed by the Chinese Communist government on the development of industry in their national economic plans. This extensive industrialization is clearly evidenced by the large share of total investment funds that was devoted to industry in their First and Second Five-Year Plans.1 In order to show the achievements, Peking has published, among other economic indicators, gross values of industrial production for the past years and the corresponding indices under various designations.2 However, there are at least two good reasons for an independent estimate of Communist China's industrial growth. First, it may serve as a check on the official claims by the Chinese Communists. Second, no meaningful comparison of the rate of industrial growth in Communist China with that of other non-communist countries can be made unless an industrial output index is recomputed for Communist China on the conventional methodological basis as employed by most non-communist countries. This paper is a preliminary report of a research project aiming to bridge this gap. Presented here are some highlights of the nature and implications of the industrial output indices we have computed for Mainland China. Owing to the limited space, the vast variety of sources of the official data and the detailed explanations on some estimates we have used in this study in order to remedy certain data deficiencies will not appear here, but they may be available on request. This paper contains two sections. Section I describes the nature of the indices and the underlying data. Section II is devoted to a discussion of some implications drawn from these indices. The indices cover a period from I949 to I959, that is, the first eleven years of the Chinese Communist regime. It was originally intended to bring the indices up to date to cover the actual production of I960. However, this was not possible due to the fact that the government in Communist China failed, by the end of I96I, to publish their economic achievements in ig60.